2019
DOI: 10.1038/s41598-019-41103-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing foot-and-mouth disease outbreaks: a methods comparison of transmission network models

Abstract: A number of transmission network models are available that combine genomic and epidemiological data to reconstruct networks of who infected whom during infectious disease outbreaks. For such models to reliably inform decision-making they must be transparently validated, robust, and capable of producing accurate predictions within the short data collection and inference timeframes typical of outbreak responses. A lack of transparent multi-model comparisons reduces confidence in the accuracy of transmission netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
0
43
1
Order By: Relevance
“…Lau's model has been developed to facilitate systematic integration of epidemiological and genetic data, jointly inferring the transmission network and genome of the transmitted virus, even when data on a subset of the infected population is unavailable (Lau et al, ). This approach appears to provide a highly reasonable inference of the transmission network for this outbreak, although the levels of model support were lower than those reported for similarly sized simulated outbreaks (Firestone et al, ), or in the original model development and verification studies (Lau et al, ). This difference in model support between the current study and the previous studies may be either due to the simulations in previous studies not capturing the full extent of the complexity of the real system, or the lower availability of genetic data in this real setting.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Lau's model has been developed to facilitate systematic integration of epidemiological and genetic data, jointly inferring the transmission network and genome of the transmitted virus, even when data on a subset of the infected population is unavailable (Lau et al, ). This approach appears to provide a highly reasonable inference of the transmission network for this outbreak, although the levels of model support were lower than those reported for similarly sized simulated outbreaks (Firestone et al, ), or in the original model development and verification studies (Lau et al, ). This difference in model support between the current study and the previous studies may be either due to the simulations in previous studies not capturing the full extent of the complexity of the real system, or the lower availability of genetic data in this real setting.…”
Section: Discussionmentioning
confidence: 71%
“…In a comparative study of transmission network models using simulated FMD outbreak data (Firestone et al, ), Lau's systematic Bayesian model was found to be the most accurate for the purpose of our investigation. Lau's model has been developed to facilitate systematic integration of epidemiological and genetic data, jointly inferring the transmission network and genome of the transmitted virus, even when data on a subset of the infected population is unavailable (Lau et al, ).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations